Work environment affects patient safety climate in a government hospital - Dyah Utari; Syahrul Meizar Nasri (Intelektual Pustaka Media Utama, 2021)
The work environment becomes one of the motivations for someone to work. The climate of working environment is very important for a person, especially for medical staffs who actually handle and deal with sick people. Medical officers are required to always be friendly, agile, discipline and polite in front of patients thus the patient feels comfortable and quiet. This study aimed to analysis the relationship between work environment and patients’ safety climate. This study was conducted with questionnaires. Based on the survey results, it was revealed that the hospital environment determines the form of services provided to patients. The working environment has positive relationship to patients’ safety climate. At the hospital, there are latent conditions that may be a risk of accidents that come from heavy work load, management and inadequate supervision, work environment filled with pressure and inadequate communication systems. Work environment contributes greatly because the overall work in providing services to patients requires good teamwork.